A comparative analysis of experts' perception of critical success factors affecting virtual organisation: North American versus Polish. (20th September 2007) - Grudzewski, Wieslaw M.; Sankowska, Anna; Wantuchowicz, Monika
This paper is a pioneering attempt to analyse the critical success factors affecting Polish-US collaboration within a Virtual Organisation (VO) in the light of opinions of experts from both countries. We have explored the similarities and differences in the perception of role of the critical success factors in these countries, potential sources of these factors and implications of these sources for Polish-US mutual collaboration in the form of VO. Trust should be considered a backbone of VO's management today affecting success of this organisational form. Furthermore, the directions for future researches in this area are given.